Treating contemporary families : toward a more inclusive clinical practice - Browning, Scott; Van Eeden-Moorefield, Brad (American Psychological Association, 2022)
"Linking research with clinical practice, this text shows therapists how to do evidence-based practice when treating contemporary families. Today's families are diverse and complex, and their problems do not always improve when treatment focuses on addressing a diagnosis. To achieve successful, lasting change, therapists must help families change their patterns of interaction. This book examines several common interactional challenges that contemporary families face, such as co-parenting, divorce, intimate partner violence, blending families, and loss and bereavement. For each challenge, contributors examine research regarding the concern as well as research on multiple diverse family types, and then provide clinical examples showing how to develop interventions for these family types. With its combined focus on inclusion, social justice, and evidence-based practice, this book will help clinicians work with today's diverse families in effective, culturally responsive ways"--